Work Readiness in Final Grade Students the Theory of the Big Five Personality (Universitas Negeri Semarang, 2023)
Unemployment is one thing that has always been a threat to every country in the world. Based on the official website of the Central Bureau of Statistics (BPS), it is stated that at least less than one million students or undergraduate graduates became victims of this action. Many solutions can be made to reduce the level and number of actions, one of which is by increasing work readiness. Then the difference in work readiness that is owned by each individual or student, cannot be separated from the factors that influence it, one of which is personality. The personality of each of course has differences between individuals, because personality is one of the systems within individuals who are born sedentary. One approach in studying personality theory is the big five-personality. This study aims to provide an overview of the level of work readiness and the influence of the top five personality traits. The type of research used is correlational quantitative, with the sampling technique used is random sampling. The data analysis used is multiple linear regression with the help of data processing software. The results of hypothesis testing which was carried out simultaneously showed a significance of 0.000, where there was an influence between the big five-personality on work readiness. then obtained through a test of the coefficient of determination of 33.3% or 69.2% influenced by other factors not explained in this study. The results of hypothesis testing which was carried out partially included in the extraversion dimension with a significance of 0.000 (p <0.05) which means a positive and significant effect on the work readiness variable.